Reconceptualising the Scholarship of Marketing Education–Some Futurescapes. Issue 2 (May 2018) - Snuggs, Elizabeth; Jevons, Colin
Teaching is an important part of marketing academics' work. However research into the scholarship of marketing education (SoME) has not enjoyed the same standing as discipline-based research, a regrettable gap. We present comparative data from other business disciplines, which all value educational research higher than the marketing discipline does. We then discuss the underlying factors and collate various scenarios into three futurescapes as bases for discussion of how to increase SoME's value and reputation in a rapidly-changing environment.